The Urgency of Developing Students’ Numeracy Skills: A Needs Analysis Study as a Foundation for Educational Design Research - Jayanti Putri Purwaningrum; Sugiman Sugiman; Sri Andayani (Jurnal Penelitian dan Pembelajaran Matematika, 2026)
Numeracy skills are an essential competency for solving problems in daily life. However, the development of mathematics learning remains a challenge today. Therefore, a study is needed that not only describes students’ numeracy skills but also identifies development needs based on empirical data. This study employed a mixed-methods approach combining quantitative and descriptive qualitative methods, based on an analysis of students’ responses to numeracy problems and interview data. The subjects who participated in the numeracy test in this study were 146 seventh-grade students from five junior high schools in Kudus Regency, selected using purposive sampling, while the subjects for the interviews consisted of 15 students and 5 mathematics teachers. The results of this study indicate variations in students’ numeracy achievement across indicators, reflecting differences in the level of mastery in applying mathematical concepts across contexts. These variations provide a basis for identifying more specific needs for the development of students’ numeracy skills. These findings indicate that mathematics instruction has not yet optimally facilitated the development of thinking processes that require comprehensive numeracy skills. The implications of this research highlight the urgency of developing learning designs that are more targeted, contextual, and aligned with students’ ways of thinking. Such designs should be developed based on real needs to support the development of students’ numeracy skills more effectively